2023
DOI: 10.3390/vaccines11020244
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Liver Regeneration in Patients Who Have Undergone Living Donor Hepatectomy for Living Donor Liver Transplantation

Abstract: Background: Inflammation and the associated immune pathways are among the most important factors in liver regeneration after living donor hepatectomy. Various biomarkers, especially liver function tests, are used to show liver regeneration. The aim of this study was to evaluate the course of liver regeneration following donor hepatectomy (LDH) by routine and regeneration-related biomarkers. Method: Data from 63 living liver donors (LLDs) who underwent LDH in Inonu University Liver Transplant Institute were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In LDLT, donor liver regeneration is also essential in determining the procedure's success. A prospective study by Satilmis B et al [ 75 ] analyzed preoperative and postoperative laboratory data from 63 donors. It indicated that PIVKA-II, one of the liver regeneration-associated markers, was significantly increased on the third postoperative day ( p = 0.007).…”
Section: Pivka-ii and Ltmentioning
confidence: 99%
“…In LDLT, donor liver regeneration is also essential in determining the procedure's success. A prospective study by Satilmis B et al [ 75 ] analyzed preoperative and postoperative laboratory data from 63 donors. It indicated that PIVKA-II, one of the liver regeneration-associated markers, was significantly increased on the third postoperative day ( p = 0.007).…”
Section: Pivka-ii and Ltmentioning
confidence: 99%